The Kanza: Travels on a Hard Trail - Wade Parsons (Symphony in the Flint Hills, 2009)
Before the famous adventurers Lewis and Clark had returned to St. Louis from their exploration of the Louisiana Purchase, another expedition was already deep into the American wilderness. On September 12, 1806, the small command of U.S. Army Lt. Zebulon Pike expedition advanced under a shadow of international intrigue and treason.
Keywords: Native Americans; Indians; peoples; tribe; tribal; Kanza; Kansas; Pawnee; Osage; war; lies; warriors; migration; government; forceful removal; change